The effect of different timing of blood transfusion on oncological outcomes of patients undergoing radical cystectomy for bladder cancer: a systematic review and meta-analysis - Ma, Si-Yang; An, Ye; Sun, Jian-Xuan; Xu, Meng-Yao; Liu, Chen-Qian; Xu, Jin-Zhou; Zhong, Xing-Yu; Zeng, Na; He, Hao-Dong; Xia, Qi-Dong; Wang, Shao-Gang (Frontiers in Oncology, 2023)
This meta-analysis and systematic review aim to analyze the association between BT and oncological outcomes of patients undergoing RC for bladder cancer, and tries to find out whether the timing of blood transfusion could also have an effect on this relationship. A total of 20 retrospective studies from online databases and other sources are identified and enrolled in this study. The results show that BT administration during RC operation or perioperative period is significantly associated with worse oncological outcomes including ACM, CSM and DR.